A Note on New Records of Ferns at Ayer Hitam Forest Reserve, Johor, Malaysia - GBENGA FESTUS AKOMOLAFE; ZAKARIA RAHMAD; FARAH ALIA NORDIN; RUSLY ROSAZLINA (Borneo Journal of Resource Science and Technology, 2022)
On a scientific expedition to Ayer Hitam Forest Reserve at Muar, Johor, Malaysia, 71 fern species belonging to 16 families and 25 genera were collected and identified. Fifty-one of the ferns are native to Peninsular Malaysia while the remaining 20 are non-native. Five newly recorded fern species in Johor, Southern Peninsular Malaysia, namely Angiopteris helferiana, Lindsaea trichomanoides, Lomariopsis brackenridgei, Pteris umbrosa and Pteris cretica were briefly described.